A note on the new species of the genus Isopsera (Orthoptera: Phaneropteridae: Phaneropterinae) from India - Nagar, Rajendra; Mal, Jhabar; Swaminathan, R. (Zootaxa, 2015)
A new species of the genus, Isopsera: Isopsera arcuata Nagar, Mal, Swaminathan sp. nov. (Orthoptera:Phaneropteridae Burmeister, 1838; Phaneropterinae Burmeister, 1838) is described. The holotype (♂) was collected from South India: Coimbatore (Tamil Nadu). The geographical location had the following specifications: 12058 N 77035E 930MSL South India. The described species differs from the two closely related species, I. caligula Ingrisch and I. spinosa Ingrisch, based on the structure of the male sub-genital plate, cerci and stridulatory file on the left tegmen.